PENGARUH METODE DAN LAMA CURING TERHADAP KARAKTERISTIK DAUN PANDAN WANGI (Pandanus amaryllifoliusRoxb.) - Pungki Wiraguna, I Gusti Ngurah; Wartini, Ni Made; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 2 (2015): Juni, 2015)
This study aims to determine the influence of curingmethod and time of curingon the characteristics of “daun pandan wangi”and obtain curingmethod and time of curingthat was able to produce the best characteristics of “daun pandan wangi”. This experiment was factorial experiment using a randomized block design with 2 factors. The first factor was the curing method consists of two methods: natural curing, andcuringoven. The second factor was a long curingconsisting of 3 levels : without curing2 days, and 4 days. Thus obtained 6 treatment combinations. Each treatment was classified into3, based on the time of implementation in order to obtain 18 units experiment. Objective dataanalyzed using ANOVA followed by Duncan test whereas subjective data were analyzed with the Friedman test. The best treatment was a treatment that produced “daun pandan wangi” most powerful aroma. The results showed interaction, the old methods of curingand curinghad significant effect on weight of “daun pandan wangi”, moisture, reducing sugar and total acid. Interaction significant, curingmethod was highly significant and long curingeffect was not significant to the total N of “daun pandan wangi”. Interaction, the old methods of curingand curingdoes not significantly affect the pH of “daun pandan wangi”. Natural curingmethod 2 days and longer curing2 days with the characteristics 71,67% moisture content, 0,033% sugar reduction, 1,600% total N, 0,217 meq NaOH/g total acid and pH of5,933 hedonic aroma of 5.48 betweenrather to like and the strongest of aroma 1,45.
Keywords: 48